Investigation of anticorrosion properties of epoxy GO nanocomposites spin coated Aluminum Alloy 7075. (26th May 2022) - Gaur, Mulayam S; Raghav, Rajesh K; Sagar, Rohan; Tiwari, R.K.
The bisphenol A diglycidyl ether-polyaminoamide (epoxy resin)–graphene oxide (GO) nanocomposites have been prepared by chemical methods. The aim of this study is to produce epoxy –GO coatings on Aluminum Alloy 7075 and study the anticorrosion properties. Thin films have been characterized by scanning electron microscope – Energy Dispersive X-rays Spectroscopy (EDX) and Raman spectra. Raman spectra show the successful bonding of GO functional groups with epoxy. The composition of epoxy and GO is characterized by EDX. The Tafel plots were undertaken for analysis of corrosion of coating material. Therefore, the reduction of corrosion current of epoxy–GO nanocomposites coated Al alloy 7075 show its superior corrosion resistance properties. This is further confirmed by electrochemical impedance spectroscopy and potentiodynamic polarization. The very high value of low frequency impedance modulus (i.e. 10 10 Ω cm 2 ) shows surprising anticorrosive effect on coating. The epoxy–GO spin coating in Al Alloy 7075 is significantly reduces the corrosion current density ( Icorr ) and corrosion rate due to anticorrosion properties of GO.